ANALISIS HUBUNGAN BERBAGAI FAKTOR DENGAN EFEKTIFITAS DAN EFISIENSI E-PUSKESMAS DI PUSKESMAS PAYUNG KABUPATEN KARO TAHUN 2023 - Bangun, Aguste Comte; Sinaga, Jon Piter; Sembiring, Bunga Mari (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Public Health Center of Payung district Karo is a Rural Health Center has been providing patient services using e-PUSKESMAS application since 2023 and has been connected to SATU SEHAT since December28th 2023. The aimed of the research is to analyze the relationship between health workers' perceptions, health workers' education level, health workers knowledge, as well as facilities and infrastructure on effectiveness and efficiency in implementing e-PUSKESMAS in Public Health Center of Payung by using qualitative research that conducted from November 2023 to March 2023. The sampling of the research used the Exponential Non-Discriminatory Snowball with the Sampling technique with 7 informants consisting of one head of community health center, one administrative person, one person from registration, one person from service, one person from laboratory, one person from pharmacy and one patient as triangulation informants. The results of the analysis to conclude that e-PUSKESMAS is effective to supporting the data-based and efficient decision making because it speeds up the work of health workers and reduces administrative costs and increases the satisfaction of patients seeking treatment at Public Health Center of Payung. The small number of health workers with bachelor's education levels and lack of training, as well as the limited number of laptops causes health workers to be less effective and efficient use of e-PUSKESMAS in serving patients.It is recommended for the Public Health Center Management to carry out Learning by doing by creating an e-PUSKESMAS operational module that is easy to understand and creating a ToT (Training of Trainer) program, so that the quality of service is more effective. Providing laptop facilities in each service unit to increase the efficiency of e-PUSKESMAS. The Karo Health Service needs to monitor regularly and the monitoring results are immediately implemented in the provision of infrastructure, so that patient services using e-PUSKESMAS are more effective and efficient at Public Health Center of Payung.